(untitled) (قضايا سياسية, 2025)
Abstract The research delved into the details of the Syrian-Iranian strategic partnership from its inception to the present day, attempting to arrive at predictions about the future of the partnership between the two countries in light of the existence of mutual interests. Syria viewed Iran as a country of significant strategic weight, while the Iranians viewed Syria as an important strategic partner in the region. The Syrian crisis, which erupted in 2011, served as a springboard for a heightened strategic partnership between Syria and Iran, following the significant support Syria received from Iran. This was followed by the 2024 regime change, which led to a clear decline in the strategic partnership between Syria and Iran. The study included future scenarios for the Syrian-Iranian strategic partnership in light of the transformations witnessed in the region, and the implications of this for regional security and the preservation of stability and balance in the region. This is particularly true given Iran's commitment to maintaining its presence in Syria, and the importance of this for Syria, which continues to need Iran to build balanced strategic relations within its regional environment.